Evaluation of the Efficacy of Two New Biotechnological-Based Freeze-Dried Fertilizers for Sustainable Fe Deficiency Correction of Soybean Plants Grown in Calcareous Soils - Ferreira, Carlos M. H.; López-Rayo, Sandra; Lucena, Juan J.; Soares, Eduardo V.; Soares, Helena M. V. M. (Frontiers in Plant Science, 2019)
Currently, fertilization with synthetic chelates is the most effective agricultural practice to prevent iron (Fe) deficiencies in crops, especially in calcareous soils. Because these compounds are not biodegradable, they are persistent in the environment and, so, there is the risk of metal leaching from the soils. Thus, new, more environmental-friendly efficient solutions are needed to solve iron deficiency-induced chlorosis (IDIC) in crops grown in calcareous soils. Therefore, the central aim of this work was to prepare new freeze-dried iron products, using a biotechnological-based process, from two siderophores bacterial (Azotobacter vinelandii and Bacillus subtilis) cultures (which previously evidenced high Fe complexation ability at pH 9) and test their ability for amending IDIC of soybean grown in calcareous soils. Results have shown that A. vinelandii iron fertilizer was more stable and interacted less with calcareous soils and its components, than B. subtilis one. This behaviour was noticeable in pot experiments where chlorotic soybean plants were treated with both fertilizer products. Plants treated with A. vinelandii fertilizer responded more significantly and comparable to the positive control, ethylenediaminedi(o-hydroxyphenylacetic acid (o,o-EDDHA), than those treated with B. subtilis one, when evaluated by their growth (20 % more dry mass than negative control) and chlorophyll development (30 % higher chlorophyll index than negative control). On average, iron content was also greater on A. vinelandii treated plants than on B. subtilis treated ones. Our results suggest that this new siderophore-based formulation product, prepared from A. vinelandii culture, can be regarded as a viable alternative for replacing the current non-green Fe-chelating fertilizers envisaging a sustainable and environmental-friendly mending IDIC of soybean plants grown in calcareous soils.